Agent-based modeling and simulation for business systems ; Agent-based simulation and validation for oil refinery supply chain (II) - Chia, Louis (2015)
Traditional models of supply chain such as equation-based modeling are inadequate and applicable only to certain functions of the supply chain. As supply chains become more complex, the agent-based modeling paradigm appears to be more able to model supply chains. An agent-based simulation model of an oil refinery supply chain is built by LesCas and then evaluated by benchmarking. This paper documents the design and modeling of building an agent-based model as well as the benchmarking results. The results showed that the model developed was valid to some extent as it was able to reproduce similar results comparable with the results from the Repast Model. Based on the results and findings from the model developed, a set of recommendations was made to enhance the LesCas software. The project team also proposed a comparability criterion to allow for more flexible benchmarking.